Penerapan Restorative Justice dalam Perkara Narkotika di Indonesia - Haposan Sahala Raja Sinaga (CV Rewang Rencang, 2021)
The purpose of this study is to examine the application of Restorative Justice in narcotics cases in Indonesia with normative juridical research methods. The results showed that Restorative Justice can be applied to narcotics addicts, abusers, victims of narcotic abuse, narcotics dependence, and narcotics use one day, in case of eligibility such as when caught by police investigators and / or BNN investigators found evidence of use one day and also have the results of an assessment of the Integrated Assessment Team on each filing. The existence of alternative case resolution through Restorative Justice can realize the principles of a quick, simple, and light-cost judiciary, as well as recover and/or develop physical, mental, and social suspects, defendants, or inmates in narcotics cases conducted with integrated and coordinated treatment, treatment and recovery programs.